UNIT COST ANALYSIS AND APPLICATION OF UNIT COST ANALYSIS ON CURATIVE SERVICES AT PRIMARY HEALTH CARE LEVEL (Vietnam Journal of Community Medicine, 2022)
The systematic review research analyzed the overall system by gathering documents from varioussources from January 2010 to June 2022 to describe the accounting methods for the unit cost ofcurative services at health facilities and its application at the primary healthcare level. Unit costanalysis applied to medical facilities has been widely deployed in many countries around the world.The bottom-up cost analysis study provided more accurate results but was not widely applied. Thecombination of both top-down and bottom-up methods has been curently a solution to overcome thelimitations of these methods. In Vietnam, unit cost analysis applied at primary health care was stilllimited in number of issues and mainly focus on setting of service prices and costs of diseases.
Keywords: Medical costs, unit cost, medical examination and treatment service, primary healthcare level.